Effectiveness of Compassion-Based and Mentalization-Based Interventions on Social Support and Resilience in Workers with Job Burnout - Mahmoodi Beram, Marzieh; Ghasemipirbalouti, Mohammad; Sharifi , Tayebeh (Mental Health and Lifestyle Journal, 2026)
The present study was conducted in 2024 with the aim of comparing the effectiveness of compassion-based and mentalization-based interventions on workplace social support and resilience among workers with job burnout in the Mansour Industry of Isfahan. The research employed a quasi-experimental method using a pretest–posttest design with a two-month follow-up. The statistical population consisted of workers experiencing job burnout in the Mansour Industry of Isfahan. A total of 60 participants were selected through purposive sampling and randomly assigned to three groups of 20 participants each (compassion-based intervention, mentalization-based intervention, and control group). Research instruments included the Maslach Burnout Inventory (Maslach, 1981), the Connor–Davidson Resilience Scale (Connor & Davidson, 2003), and the Workplace Social Support Questionnaire (Liu et al., 2000). The first experimental group received a compassion-based intervention over twelve 90-minute sessions, the second experimental group received a mentalization-based training package over twelve 90-minute sessions, and the control group was placed on a waiting list. Data were analyzed using repeated measures ANOVA and the Bonferroni post hoc test. The results indicated that the compassion-based intervention was effective in improving resilience and workplace social support among workers with job burnout in the Mansour Industry of Isfahan (p < .05), and this effectiveness was maintained over time (p < .05). Furthermore, the findings showed that the compassion-based intervention was more effective than the mentalization-based intervention in enhancing workplace social support and resilience among workers with job burnout in the Mansour Industry of Isfahan (p < .05). Compassion-based and mentalization-based interventions both improved resilience and workplace social support among workers with burnout; however, compassion-based therapy yielded more profound and enduring outcomes. These findings underscore the importance of integrating compassion training into workplace mental health programs to strengthen employee resilience and interpersonal support.